MECHANISMS OF ANTI-CORRUPTION MANIFESTATIONS IN THE TRANSPORT SPHERE - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the purpose of the scientific article is to summarize the results of the public expert discussion and suggest ways to reform the anti-corruption system as one of the defining areas for overcoming it. Methods: general and special scientific (special) methods were used to achieve this goal. The use of these methods allowed, based on the analysis of the real results of anti-corruption bodies, to outline ways to reform the anti-corruption system as one of the defining areas for overcoming it. Results: despite numerous studies on this issue, modern conditions dictate the need for continuous improvement of research, which is possible only if. continuous search for new ways to combat corruption in Ukraine. Combating corruption by legal means must take into account the challenges and threats posed by the aggravation of the criminogenic situation in society, the preservation of the shadow economy and the intensification of corruption; incomplete economic transformations, deepening income differentiation and, of course, imperfect legislation. Discussion: identifying ways to improve anti-corruption legislation, ensuring the unity of its application requires a balanced, responsible approach, involving in these processes not only scientists but also practitioners, representatives of public organizations. Peculiarities of the fight against corruption in the transport sphere and methods of eliminating this phenomenon are commensurate with the general ones and include: controllability of state officials, state institutions of the public; openness and transparency of decision-making at all levels of government; freedom of speech, freedom of the media and their real independence; the possibility of public control over the adoption of the most important economic and political decisions; independence of the judiciary; balance of power. The state of the fight against corruption, the level of its danger, the presence of reasoned positions of both supporters and opponents of the criminalization of declaring unreliable information requires further thorough scientific research